The use of medications for the treatment of headache during pregnancy and its consequences: a literature review - Macêdo, Carolina Helen Soares de; Lima, Rayndrick Kelryn Assis; Lima, Raynrich Kevin Assis; Santos, Isabela Cacau Sousa; Appio, Pedro Roa; Lima, Eduarda Maia; Filho, Helvécio Neves Feitosa; Furtado, Nithyananda Araújo; Carate, Caio Kacem (Headache Medicine, 2023)
Full abstract in PDF.